2015
DOI: 10.3109/02699052.2015.1042053
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from Scutellaria attenuate okadaic acid-induced neuronal damage in rats

Abstract: SSF-mediated amelioration of OA-induced neuronal damage in rats provides a rationale for assessing SSF as a means of to reducing tau hyperphosphorylation and Aβ expression in the treatment of Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…When Wistar rats were prefed with Scutellaria baicalensis stem-leaf total flavonoid preparations and then amyloid beta-peptide injected into the bilateral hippocampus, resulting apoptosis was attenuated compared to control animals [16]. Baicalin also provided neuroprotection against global ischemia/reperfusion injury via activation of GABAergic signaling [17], inhibited inflammatory activation of microglia [18], protected against glutamate/NMDA excitotoxicity [19], mitigated okadaic acid-induced neuronal damage [20], protected against oxidative stress-induced DNA damage by upregulating the DNA repair system [21], and reduced hippocampal neuronal damage in global cerebral ischemia model through the inhibition of MMP-9 activity [22]. The result of baicalin neuroprotection was also observed as improved cognitive function in senescent mice [23].…”
Section: Introductionmentioning
confidence: 99%
“…When Wistar rats were prefed with Scutellaria baicalensis stem-leaf total flavonoid preparations and then amyloid beta-peptide injected into the bilateral hippocampus, resulting apoptosis was attenuated compared to control animals [16]. Baicalin also provided neuroprotection against global ischemia/reperfusion injury via activation of GABAergic signaling [17], inhibited inflammatory activation of microglia [18], protected against glutamate/NMDA excitotoxicity [19], mitigated okadaic acid-induced neuronal damage [20], protected against oxidative stress-induced DNA damage by upregulating the DNA repair system [21], and reduced hippocampal neuronal damage in global cerebral ischemia model through the inhibition of MMP-9 activity [22]. The result of baicalin neuroprotection was also observed as improved cognitive function in senescent mice [23].…”
Section: Introductionmentioning
confidence: 99%
“…Genistein has a similar structure as estrogen. Through binding to the estrogen receptor, genistein exerts strong activity, and it is considered to be an active phytoestrogen [8,9]. An increasing number of studies have shown that genistein is involved in inducing cancer cell apoptosis, inhibiting cell proliferation, suppressing angiogenesis and inhibiting colorectal cancer metastasis [10].…”
Section: Agingmentioning
confidence: 99%
“…Natural flavonoids are a class of variable polyphenolic structures that confer favorable biochemical and antioxidant effects in various diseases (Kumar & Pandey, 2013; Panche et al, 2016). Flavonoids reduce oxidative stress and inflammation in neuronal cells (Cho et al, 2012; Frandsen & Narayanasamy, 2018; Ishige et al, 2001; Kling et al, 2014; Pavlica & Gebhardt, 2010) and rat models (Shang et al, 2006; Zhang et al, 2015). Several flavonoids protect against MG‐induced mitochondrial dysfunction and apoptosis in neuronal cell lines (Jiang et al, 2016; Liu et al, 2017; Wang et al, 2014; Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%